Comparative critique on the design parameters and their effect on the performance of S-rotors - Al-Kayiem, H.H. (Elsevier Ltd, 2016)
S-rotors, which currently have numerous configurations, after the introduction of the early type by Savonius, are low-cost and simple devices used to harness wind energy for stand-alone power systems. Although the power coefficient of S-rotors is comparatively low, geometric parameters, such as overlap ratio, aspect ratio, number of blades, number of stages, and blade profile, are highly affect its performance. Optimization of the rotor design requires further understanding on how each parameter influences the rotor performance. Therefore, this comparative critique on the design parameters is conducted to highlight the performance improvement of S-rotors via the optimization of the geometric parameters. In addition, cost analysis on the small scale wind power generation has been overviewed. The influence, of the modification of the blade profiles and flow concentration setups, on the performance is also discussed with the aid of drawings, comparison table, and graphical representations. The critique on the dynamic and static characteristics of S-rotors is presented in this study to improve the characteristics of S-rotors as stand-alone electric power systems for remote rural communities. The average Cp of S-rotors under open flow conditions is ranging from 0.037 to 0.37. However, the Cp of S-rotors with external flow guides can reach up to 0.52. Â© 2016 Elsevier Ltd